Optimizing growth factor induction of tenogenesis in three-dimensional culture of mesenchymal stem cells - Ibtesam Rajpar; Jennifer G Barrett (Journal of Tissue Engineering, 2019)
Adult tissue stem cells have shown promise for the treatment of debilitating tendon injuries. However, few comparisons of stem cells from different tissue sources have been made to determine the optimum stem cell source for treating tendon. Moreover, it is likely that the application of tenogenic growth factors will improve tendon stem cell treatments further, and a comprehensive comparison of a number of growth factors is needed. Thus far, different types of stem cells cannot be evaluated in a high-throughput manner. To this end, we have developed an approach to culture mesenchymal stem cells isolated from bone marrow in collagen type I hydrogels with tenogenic growth factors using economical, commercially available supplies. To optimize growth factors for this assay, FGF-2, TGF-β1, IGF-1, and/or BMP-12 were tested singly and in novel combinations of (1) BMP-12 and IGF-1, (2) TGF-β1 and IGF-1, and/or (3) BMP-12 and FGF-2 over 10 days. Our data suggest that BMP-12 supplementation alone results in the strongest expression of tendon marker genes, controlled contractility of constructs, a higher degree of cell alignment, and tendon-like tissue morphology. This easy-to-use benchtop assay can be used to screen novel sources of stem cells and cell lines for tissue engineering and tendon healing applications.